Handgrip force of maltreating mothers in reaction to infant signals. (February 2015) - Compier-de Block, Laura H.C.G.; Alink, Lenneke R.A.; Reijman, Sophie; Werner, Claudia D.; Maras, Athanasios; Rijnberk, Corine; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.
Abstract: Handgrip force responses to infant signals were examined in a sample of 43 maltreating and 40 non-maltreating mothers. During a standardized handgrip paradigm, mothers were asked to squeeze a handgrip dynamometer at maximal and at half of their maximal handgrip strength while listening to infant crying and laughter sounds. Maltreating mothers used excessive force more often while listening to infant crying and laughter than non-maltreating mothers. Of the maltreating mothers, only neglectful mothers ( n = 20) tended to use excessive force more often during crying than non-maltreating mothers. Participants did not rate the sounds differently, indicating that maltreating mothers cannot be differentiated from non-maltreating mothers based on their perception of infant signals, but show different behavioral responses to the signals. Results imply that, in response to infant signals (i.e., crying or laughing), maltreating mothers may be insufficiently able to regulate the exertion of physical force.